ANALYSIS OF FATIGUE WORK FACTORS IN CONSTRUCTION WORKERS OF PT. MANDALA PUTERA PRIMA IN THE BANK INDONESIA KARAWANG PROJECT IN 2023 - Okbi Mardian (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Labor as an investment asset needs to work properly and correctly, among others, by taking into account the factors that may cause fatigue. As is known, that by increasing organizational performance through handling ergonomic work procedures is one way to increase productivity and prevent work accidents. Research to find out the analysis of fatigue work factors in construction workers of PT. Mandala Putera Prima in The Bank Indonesia Karawang Project Tahun 2023. This type of analytic observational research with a cross-sectional study approach. The result from this research is 90.5% of workers aged <30 years experience more symptoms of work fatigue with a p-value> 0.05, namely 0.661, 95.0% have a working period of 2-5 years, experience symptoms of work fatigue with a p-value> 0.05, namely 0.708, duration of work > 8 hours, 90.5% experienced symptoms of work fatigue with a p value> 0.05, namely 0.825 and heavy workload with symptoms of work fatigue, 80.0% experienced symptoms of work fatigue with a value of p> 0.05, namely 0.218. The risk of work fatigue in construction worker activities has a risk of the symptoms of the disease occurring. Workers with a risk of symptoms of work fatigue recommend that to reduce the risk of work fatigue workers get used to getting enough sleep 7-8 hours a day and eating a balanced diet (mainly vegetables and fruits).